KAJIAN KONDISI LINGKUNGAN TEMPAT PENELURAN PENYU DI DESA PASIE LEMBANG, ACEH SELATAN - Dewi Fitriani; Nabil Zurba; Edwarsyah Edwarsyah; Neneng Marlian; Roni Arif Munandar; Citra Dina Febrina (Journal of Aceh Aquatic Sciences, 2021)
Indonesian marine waters have habitats for six species of sea turtles from seven species in the world, namely green turtles (green turtles, Chelonia mydas), olive ridley turtles (olive ridley, Lepidochelys olivacea), loggerhead turtles (loggerhead, Caretta caretta), hawksbill turtles (hawksbill, Eretmochelys imbricata), leatherback turtles (leatherback, Dermochely coriacea) and flatback turtles (flatback, Natator depressus). All types of turtles in Indonesia are protected under PP. 7 of 1999 concerning Preservation of Plant and Animal Species and PP No. 8 of 1999 concerning the Utilization of Wild Plant and Animal Species, which means that all trade in a state of life or death is prohibited. This is because almost all turtle species in Indonesia have experienced a decline in population so they are categorized as endangered